The export of Russian gas to Europe: breaking up the monopoly of Gazprom - Marina Tsygankova (Statistics Norway, Research Department, 2007)
Having exports from more than one Russian gas producer has been an important issue in the Russian-EU energy dialogue during the last decade. Nevertheless, in June 2006, Russian Federal law legalized the de facto export monopoly of Gazprom. Political and commercial interests have regularly explained the Russian strategy for the European gas market. However, it is important that economic efficiency is also taken into account. Economists often evaluate the efficiency of a policy through its effect on national welfare. In this paper, I examine both theoretically and numerically whether a liberalization of Russian gas exports would increase Russian national welfare, given that the Russian domestic market is already deregulated. The results of the paper show that the dominant position of Gazprom in the Russian gas industry might stimulate the government to support Gazprom's export monopoly. The market share of independent producers in the Russian gas market would have to be significantly increased for Russian export liberalization to be welfare enhancing.
Keywords: D43; D60; L13; Q38; 330; Russia; Natural gas; export; monopoly; national welfare